1998
DOI: 10.1115/1.2841386
|View full text |Cite
|
Sign up to set email alerts
|

CFD Analysis of Coverplate Receiver Flow

Abstract: The flow field in a preswirled cooling air supply to a turbine rotor has been investigated by means of CFD simulations. Coefficients for system efficiency are derived. The influences of various geometric parameters for different configurations have been correlated with the help of appropriate coefficients. For some of the most important geometric parameters of the coverplate receiver, design recommendations have been made. For the preswirl nozzles, the potential of efficiency improvement by contour design is h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Besides that, some studies on the discharge coefficient of the receiver hole which represents the losses occurring in the receiver hole were conducted by the researchers [5][6][7][8], and the results showed that a peak in discharge coefficient of receiver holes occurs at a minimum of the tangential velocity differential. Generally, besides cooling blades, the cooling air in the preswirl rotor-stator system plays roles to pressurize the cavity and cool the rotor wall of cavity.…”
Section: Introductionmentioning
confidence: 99%
“…Besides that, some studies on the discharge coefficient of the receiver hole which represents the losses occurring in the receiver hole were conducted by the researchers [5][6][7][8], and the results showed that a peak in discharge coefficient of receiver holes occurs at a minimum of the tangential velocity differential. Generally, besides cooling blades, the cooling air in the preswirl rotor-stator system plays roles to pressurize the cavity and cool the rotor wall of cavity.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Luo et al 7 numerically simulated the flow and heat transfer characteristics of a direct pre-swirl system using the realizable κ-ε turbulence model, verified with the experimental results. Then, Popp et al 8 numerically investigated the flow characteristics of the receiver hole and proposed that the relative parameters should be used to describe the aerodynamic characteristics of the rotating receiver hole.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, X. Liu [6] has studied the flow in a corotation radial inflow cavity between turbine disk and coverplate. Also, the flow field in a preswirled cooling air supply to a turbine rotor has been investigated by Oliver et al [7,8] .…”
Section: Introductionmentioning
confidence: 99%